Malaysia-Timor Leste’s Relations, 2002-2015 - Wan Shawaluddin Wan Hassan; Ramli Dollah; Diana Peters (2018)
As a new state in the international system, Timor Leste requires partners and development models to enable the country to flourish. In this regard, Malaysia with its extensive experience dealing with international issues is seen as the most appropriate model in realizing this desire. Despite the fact that Timor Leste has no strategic economic value to Malaysia, as Timor Leste is seen as a poor and newly independent state, the writer argues that Malaysia has enormous responsibilities in assisting these new independent neighbours. Hence, the main focus of this paper is to evaluate how Malaysia who has a similar experience as a former colonised state and experienced nation-building process can assist the process of forming a newly independent nation thus contributing to the peace and stability in the country as well as and at the regional level. It discusses Malaysia's commitment to the development of the Timor-Leste, and at the same time it seeks to identify current cooperation and other strategic areas of interest for both countries.